2013
DOI: 10.1177/201010581302200304
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes after Inpatient Rehabilitation in a Prospective Stroke Cohort

Abstract: Aim: Rehabilitation is proven to improve function following a stroke. The functional outcomes of stroke patients and benefits from rehabilitation are highly variable. We aim to describe functional outcomes and gains following inpatient rehabilitation post-stroke and identify factors associated with improved outcomes. Methods: In this five-years prospective study, data for 1332 consecutive stroke patients admitted to the Singapore General Hospital inpatient rehabilitation unit were charted into a custom-designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
(43 reference statements)
2
9
2
Order By: Relevance
“…The results of this study indicated that the male patients had lower functional outcome probability than female patients. This contrasted to the Ng et al (2013) who stated that female patients had worse post-stroke physical ability than male patients who were able to do physical activity independently (HR: 0.51, 95%CI:0.32-0.79). The researcher stated that the pre-stroke physical function and the symptoms of depression were important factors in the different results of the both gender recovery (Ng et al, 2013).…”
Section: Table I Basic Characteristics Of the Research Subjectscontrasting
confidence: 71%
“…The results of this study indicated that the male patients had lower functional outcome probability than female patients. This contrasted to the Ng et al (2013) who stated that female patients had worse post-stroke physical ability than male patients who were able to do physical activity independently (HR: 0.51, 95%CI:0.32-0.79). The researcher stated that the pre-stroke physical function and the symptoms of depression were important factors in the different results of the both gender recovery (Ng et al, 2013).…”
Section: Table I Basic Characteristics Of the Research Subjectscontrasting
confidence: 71%
“…According to Haigh et al (2001), numerous assessment tools have been used to measure therapy outcomes for stroke, such as the Functional Independence Measure (FIM) (Dodds et al, 1993), the Barthel Index (Mahoney and Barthel, 1965), the Rivermead Behavioural Memory Test (Collen et al, 1991) and the Medical Outcomes Study Short Form General Health Survey (SF-36) (Ware and Sherbourne, 1992). In Singapore, the FIM and the Modified Barthel Index (Shah et al, 1989) are commonly used as outcome measures for the stroke population (Chua and Kong, 1996;Ng et al, 2013). However, these scales only measure a certain domain of performance in relation to activity limitation (Unsworth, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The recovery and rehabilitation process, if not well-managed, can lead to aftereffects which will impact on the quality of lives of the patients and their families. It was reported that early rehabilitation management after acute stroke leads to better outcomes and shorter hospitalization stays [3].…”
Section: Introductionmentioning
confidence: 99%